My grandmother breaks her hip - Bamjee, Saaleha (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
A collection of narrative and confessional poems. The poems are mostly short, cinematic, physical, imagistic: moments in time. They explore the poet's own life, body, memories, and family relationships, and the tensions between power, duty, love and faith. Several poems concern the navigation of meaning and belonging in a time when international urban culture often clashes with tradition.
Keywords: Creative writing (Higher education) -- Research -- South Africa; Creative writing -- Poetry; South African poetry (English) -- Study and teaching (Higher); South African poetry (English) -- 21st century; English language -- Writing